solve the equation x^2 - 4x +2=0 by completing the square

First we put the constant number to the right side:

x^2 - 4x = -2

Next, we divide the number in front of the x term by 2 and form a new squared binomial:

(x - 2)^2 = -2 + 4 We must add a 4 to the right side to account for the 4 on the left side

(x - 2)^2 = 2

Now, we take the square root of both sides to get

x - 2 = +/- √2

x = 2 + √2

x = 2 - √2

Thanks for the quick answer !

No problem ;)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up